Flap Sliding Technique for Managing Flap Striae following Laser In Situ Keratomileusis - Khaled Abdelazeem; Mohamed A. Nassr; Hazem Abdelmotaal; Ehab Wasfi; Dalia Mohamed El-Sebaity (Journal of Ophthalmology)
Purpose. To assess the efficacy and safety of a simple, noninvasive, “flap-sliding” technique for managing flap striae following laser in situ keratomileusis (LASIK). Methods. This prospective, interventional study included eyes with post-LASIK flap striae. All eyes underwent flap sliding 1-2 days after surgery. Following flap edge epithelialisation, a cellulose sponge was used to gently slide the flap perpendicular to the striae direction. This technique allows for flap striae treatment without flap lifting, avoiding any associated lifting complications. Uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and refractive error were monitored one day after the flap-sliding procedure. Results. Fifteen eyes (15 patients) with post-LASIK flap striae were managed using the flap-sliding technique. The procedure did not successfully relocate the flap striae in 1 eye, and flap elevation and floating (using a balanced salt solution) were required. Therefore, 14 eyes were included in post-flap-sliding analyses. The UDVA improved in all patients the first day after the flap-sliding procedure was performed, with 11 of 14 eyes (78.57%) reaching an UDVA of 20/25 or better. Complications following flap sliding occurred in 2 eyes (14.29%). One eye had intraoperative epithelial abrasion, and 1 eye had residual postoperative striae outside of the optical zone. Conclusion. The flap-sliding technique is a simple, noninvasive, efficient, and safe technique for managing post-LASIK flap striae that develop after epithelial healing in the early post-LASIK period. This trial is registered with NCT04055337.